Open innovation in SMEs a bibliometric literature review using VOSviewer - Nuryakin Nuryakin; Brian Kiprop Ngetich; Valent Krishna B (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Purpose – The focus of this study is to evaluate the features of open innovation using data accessed from the Scopus online database. We are looking at two keywords: open innovation and SMEs. Design/methodology/approach – The study measured a bibliometric analysis of 1,214 articles from 157 journals during 2007-2020. Findings: The findings showed that the publication trend on open innovation kept increasing. The most cited article was Open Innovation in SMEs: Trends, Motives, and Management Challenges by Van de Vrande with 1,107 citations, followed by Lee et al. with 699 citations. The publication journal with the highest citation was Technovation and Research Policy. The United Kingdom and Italy were in the top-ranking countries for publications on this topic. The document citation category showed that Belgium ranked the highest with 1,990, followed by the Netherland with 1,212. Research limitation/implications: This study provides a literature search on open innovation and has several limitations that require future study recognition. These limitations include that databases are limited to sources originating from one database only in data collection and data synthesis. Practical implications: The practical implications provide benefits about open innovation, which can help SMEs understand open innovation and apply it as their preferred strategy in developing business. This study also allows SMEs owners and managers to understand open innovation as a strategic choice to consider as the concept is a part of the strategic intervention for their business. Originality/value: This study provides the most influential contribution and impact on the research interest of open innovation that develops from various fields, including leading researchers and their home countries. Second, a co-citation analysis addressed the second question in this research study.